Learning to Look at the Bright Side of Life: Attention Bias Modification Training Enhances Optimism Bias - Kress, Laura; Aue, Tatjana (Frontiers in Human Neuroscience, 2019)
Identifying neurocognitive mechanisms underlying optimism bias is essential to understand its benefits for well-being and mental health. The combined cognitive biases hypothesis suggests that biases (e.g., in expectancies and attention) interact and mutually enforce each other. Whereas, in line with this hypothesis, optimistic expectancies have been shown to guide attention to positive information, reverse causal effects have not been investigated yet. Revealing such bidirectional optimism-attention interactions both on a behavioral and neural level could explain how cognitive biases contribute to a self-sustaining upward spiral of positivity. In this behavioral study, we hypothesized that extensive training to direct attention to positive information enhances optimism bias. To test this hypothesis, for two weeks 149 participants underwent a daily on-line 80-trial attention bias modification training (ABMT) to accepting and away from rejecting faces or a neutral control training. Participants in the ABMT group were instructed to click as quickly as possible on the accepting face among 15 rejecting faces randomly displayed on a 4-by-4 matrix; participants in the control group were instructed to click on the five-petaled flower depicted among 15 seven-petaled flowers. Comparative optimism bias and state optimism were measured via questionnaires before, after one, and after two training weeks. ABMT enhanced comparative optimism bias, whereas control training did not. Our findings reveal that ABMT to positive social information causally influences comparative optimism bias and may, thereby, trigger the biases’ benefits for well-being and mental health. These results can (a) stimulate future neurophysiological research in the area of positive psychology and (b) reveal an innovative low-cost and easy-to-access intervention that may support psychotherapy in times of rising numbers of patients with psychological disorders.